Life table parameters of Toxoptera aurantii (Hemiptera: Aphididae) on Citrus sinensis - الرستم, آمنة; نبيل أبو كف,; إنصاف عاقل, (Latakia University Journal -Biological Sciences Series, 2024)
Life table parameters of the black citrus aphid Toxoptera aurantii (Boyer de Fonscolomb, 1841) were studied in the laboratory, where they were reared at a temperature 25±1°C, relative humidity 65±5%, and photoperiod (8:16) [D:L], in the Economic Insects Laboratory at the Faculty of Agricultural Engineering, Tishreen University, Lattakia, Syria, in the Season 2021-2022, and the parameters were calculated using the TWOSEX-MSChart program. The results showed Value the following parameters: Intrinsic rate of increase (r) 0.21±0.0076 Female/female/day, Finite rate of increase (λ) 1.24±0.0094 day, net reproductive rate (R0) 22.37±1.9433 Female/female/generation, gross reproductive rate (GRR) 42.44±1.479 individuals/offspring, Generation time (T) 14.632±0.281 day, The doubling time (DT) 3.26 day, Fecundity (F) 30.23±1.925 nymph/female, Survival rate (lx) = 0.97, Total developmental times of immature (nymph) mean 7.46±0.17, Adult pre-reproduction period of female adult (APRP) 0.46±0.08, Total pre-reproduction period of female counted from birth (TPRP) 7.96±0.19, The Mean age of the adult female 27.28±1.11 day, Results of this study are useful to understand the Dynamic numbers of the black citrus aphid.